Digital-Based Religious Moderation: Analyszing Ustadz/Kyai’s Dakwah Content on Youtube - Shofiyuddin, Haris; Alindah, Lutfiyah; Juma’, Juma’ (Aqlam: Journal of Islam and Plurality, 2024)
Abstract: YouTube serves as a media platform that offers not only knowledge and education but also a means for sharing religious content. However, not all religious content on YouTube conveys messages of religious moderation. There is a substantial amount of content that promotes rigidity and violence in understanding religion, potentially influencing individuals' religious attitudes. This study aims to explore religious moderation within the da'wah content of ustadz or kyai on Youtube. This qualitative research employs Van Dijk's discourse analysis approach. The study reveals that the da'wah content by Hanan Attaki, Adi Hidayat, Khalid Basamalah, and Gus Miftah predominantly incorporates pillars of thought by connecting the meanings of verses, hadiths, or historical contexts. The pillars of action are exemplified through acts of tolerance and wisdom in dealing with differences. The implementation of these pillars of religious moderation in their da'wah content is primarily confined to national commitment and the strengthening of tolerance.Keyword: moderation, Youtube, ustadz/kyai Abstrak: Youtube merupakan sebuah media platform yang tidak hanya menyuguhkan seputar pengetahuan atau pendidikan, tetapi juga sebagai sarana sharing agama. Namun, tentu tidak semua konten YouTube agama mengandung pesan-pesan moderasi beragama. Ada banyak konten YouTube yang justru menyuguhkan kekakuan dan kekerasan dalam memahami agama. Sehingga, akan berpengaruh terhadap sikap beragama seseorang. Dalam hal ini, penelitian ini berusaha memotret moderasi beragama dalam konten dakwah ustadz atau kyai di YouTube. Penelitian ini adalah penelitian kualitatif dengan pendekatan analisis wacana Van Dijk. Hasil penelitian menunjukkan bahwa konten dakwah yang disampaikan oleh Hanan Attaki, Adi Hidayat Khalid Basamalah, dan Gus Miftah lebih banyak menerapkan pilar pemikiran, yaitu dengan mengkaitkan makna ayat, hadist, atau bahkan sejarah. Sedangkan pilar perbuatan lebih pada percontohan hablum minannas, baik bersikap toleransi maupun bijak dalam perbedaan. Adapun implementasi dari pilar-pilar moderasi agama dalam konten dakwah ini adalah pada batas komitmen bernegara dan penguatan toleransi semata.Kata Kunci: Moderasi, Youtube, ustadz/kiai